2015
DOI: 10.1097/pcc.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Children With Pediatric Acute Respiratory Distress Syndrome

Abstract: The Consensus Conference developed pediatric-specific recommendations related to monitoring children with pediatric acute respiratory distress syndrome. These include interpreting monitored values such as tidal volume using predicted body weight, monitoring tidal volume at the end of the endotracheal tube in small children, and continuous monitoring of exhaled carbon dioxide in intubated children with pediatric acute respiratory distress syndrome, among others. These recommendations for monitoring in pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 111 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…The relatively new concept of driving pressure was not addressed by PALICC 2015 16 as a parameter to be monitored in pediatric ARDS due to the lack of pediatric data. 25 The PALICC recommendations had suggested limiting tidal volume to 5-8 mL/kg (3-6 mL/kg for severe disease), aiming to limit PIP. We feel that monitoring driving pressure may guide clinicians to individualize the tidal volumes and to decide when to use or accept lower tidal volumes than the conventional 6 mL/kg in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively new concept of driving pressure was not addressed by PALICC 2015 16 as a parameter to be monitored in pediatric ARDS due to the lack of pediatric data. 25 The PALICC recommendations had suggested limiting tidal volume to 5-8 mL/kg (3-6 mL/kg for severe disease), aiming to limit PIP. We feel that monitoring driving pressure may guide clinicians to individualize the tidal volumes and to decide when to use or accept lower tidal volumes than the conventional 6 mL/kg in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, VT as measured in some ventilators is lower than the real volume(24). Investigation of measured lung volumes, compared to those calculated from ABW versus PBW in children, and whether the PBW use has an effect on pediatric ARDS outcomes, is a priority(25). Provocatively, a recent meta-analysis (26) suggested that unlike the ARDSNet trial in adults, VT is not associated with mortality in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no recommendations related to weaning children from the ventilator that can be supported by rigorous evidence, and our review does not provide any definitive answers (84). There is a need to generate more evidence related to pediatric ventilator liberation so that any recommendations can have stronger certainty (85, 86). Many patients do not need a weaning strategy, as they are likely to pass a SBT on the first attempt and can successfully be extubated if other ERT criteria are met.…”
Section: Clinical Implications and Directions For Further Researchmentioning
confidence: 99%